Pengelolaan Limbah Bahan Berbahaya Dan Beracun (B3) Di Tempat Penyimpanan Sementara PT. X - Fernanda Pratama Putra; Natalina Natalina; Hardoyo Hardoyo (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The management of B3 waste must be conducted effectively before disposal into the environment to prevent environmental hazards and threats to human health. The objective of this internship is to identify B3 waste and assess its management in compliance with prevailing regulations. Data collection methods include both primary and secondary data. Primary data is gathered through observation, interviews, and documentation, while secondary data is obtained from legislative regulations, company profiles, and B3 waste data for the of PT. X. The result of identifying the more dominant type of hazardous waste B3 at PT. X of used Oil B3 waste out of the total B3 waste entering the TPS. The management of B3 waste at PT. X includes collection, storage, and transportation. All B3 waste is entirely handed over to third parties for processing/utilization. All processes of B3 waste management at PT. X are technically in accordance with the applicable hazardous waste regulations.